Peran Guru Dalam Membentuk Karakter Tanggung Jawab Melalui Pembelajaran Tematik PPKN Siswa Kelas Va - Aprilianti, Nerliana; Juarsa, Osa; Lusa, Herman (Universitas Bengkulu, 2025)
This research endeavors to elucidate the influence of educators in cultivating a sense of responsibility through thematic learning incorporating PPKn for students in class VA at Elementary School 41 Bengkulu City. The nature of this investigation is descriptive qualitative. The focus of inquiry is the teacher of class VA. Tools for this study include observation and interview protocols. Data acquisition methods involve observing and conducting interviews. The gathered information was evaluated through the processes of data collection, data refinement, data visualization, and conclusion formulation/validation. This study centers on two key functions of the teacher in developing responsible character: the teacher as a motivator and as a facilitator. Findings indicate that the educator's role as a motivator involves providing encouragement and guidance to students while delivering lessons. As a facilitator, the teacher fosters an engaging environment and supplies resources in the form of learning media and instructional materials. The study concludes that the VA class teacher successfully fulfills their role as both a motivator and facilitator in nurturing responsible character at State Elementary School 41 Bengkulu City.